Chordoma Spontaneous Regression After COVID-19 - Luis Fernando Moura da Silva Junior; Gyl Eanes Barros Silva; Marcos Adriano Garcia Campos; Antonio Augusto Lima Teixeira Júnior; Ramon Moura Santos; Orlando José dos Santos; Natalino Salgado Filho (Viruses)
Chordomas are a low-to-intermediate-grade slow-growing subtype of sarcoma, but show propensity to grow and invade locally with recurrence and metastasis in 10–40% of cases. We describe the first case of spontaneous regression of a solid tumor (histologically and immunohistochemically proven chordoma) after COVID-19. A female patient with clival chordoma underwent occipitocervical fixation prior to tumor resection. In the early post-operative stage following the arthrodesis procedure, she was diagnosed with COVID-19. Six months after COVID-19, she finally came back for endoscopic endonasal resection of the tumor and pre-operative MRI surprisingly showed 98.9% regression of the tumor volume. Tumor resection was performed, and both histopathological and immunohistochemistry confirmed diagnosis of chordoma with positive brachyury levels. She showed improvement of right hemiparesis and left-sided tongue palsy. The tumor was comprised of tumor-infiltrating inflammatory cells. CD3 and CD68 were positive, suggesting the presence of T-lymphocytes and macrophages. CD20 and CD56 were negative, suggesting the absence of B-lymphocytes and NK-cells. The authors believe that the onset of COVID-19 exacerbated the patient’s immune response and improved anti-tumor immunity. It was concluded that T-cells, which are involved in the COVID-19 immune response and were found infiltrating the tumor, acted as a critical pathway to this event. Further studies are encouraged in order to gain a better understanding of the SARS-CoV-2–chordoma interaction.